Dynamic capabilities for ecosystem orchestration : A capability-based framework for smart city innovation initiatives - Linde, Lina; Sjödin, David; Parida, Vinit; Wincent, Joakim (Elsevier, 2021)
Firms are faced with increased dynamism due to rapid technological development, digitalization, and sustainability requirements, creating novel opportunities for ecosystem innovation. This is particularly prevalent in smart city contexts where initiatives concerning, for example, energy efficient buildings and smart energy grids drive new kinds of ecosystem formation. Orchestrating emerging innovation ecosystems can offer a path to sustained competitive advantage for ecosystem leaders. Yet, it calls for the development of new capabilities to sense, seize, and reconfigure digitalization opportunities in a highly dynamic ecosystem environment. Yet, prior research lacks insights into the dynamic capabilities and routines required for ecosystem innovation. Therefore, this study investigates how firms can develop dynamic capabilities to orchestrate ecosystem innovation and, thus, gain from it. Through a multiple case study of smart city initiatives, we offer insights into the specific micro-foundations or sub-routines underlying the ecosystem leader's sensing, seizing, and reconfiguring capabilities, which are necessary to orchestrate ecosystem innovation. We develop a capability-based framework demonstrating three orchestration mechanisms – namely, configuring ecosystem partnerships, value proposition deployment, and governing ecosystem alignment. Our findings carry implications for the literature on innovation ecosystems and dynamic capabilities, as well as for managers.
Keywords: Ecosystem innovation; Smart cities; Digitalization; Digital servitization; dynamic capabilities; fi=Strateginen johtaminen|en=Strategic Management|